CREATIVE ECONOMY PRACHUAPKHIRIKHUN PROVINCE STUDYOF OPPORTUNITYAND FEASIBILITYIN STABILITYAND CREATION ADDED VALUEOFSMALLAND MEDIUM BUSINESSGROUPS - Weerawan Pinchumpholsang, Tassanee Singchareon,Somjai Srinet, BunditAnuyahong, WipaneePengnate, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were to study 1) opportunities and possibilities of small and medium-sized businesses in PrachuapKhiri Khan Province; 2) opinions of consumers towards business running to meet the needs of tourism in PrachuapKhiri Khan Province; and 3) guidelines for developing and promoting small and medium-sized businesses in PrachuapKhiri Khan Province to add value to the economy of business groups and incomes of local community. Samplings of this study was gathered using purposive sampling method of 60 cases with in-depth interviews of seven business fields, food, confectionery, beverages, chili paste, processed seafood, cafes and local clothing.The results were presented as: 1) Female entrepreneurs were more than males, under 30 years old, bachelor's degree with business experiences of 1-5 years, and had 1-3 familymembers; 2)Local clothing business was the lowest investment budget while food business was the highest income, return and the lowest cost; and 3) Beverage business was the fastest payback (11 months),food business was maximum return on investment (118.62%, present value 121,687.00 baht), seafood processed food was the highest rate of return on sales (39.00%), local clothing business was the highest profit (index 1.09 times to investment budget), and chili paste business was the highest net yield (81.669%).